Skills and Jobs in Brazil : An Agenda for Youth - Almeida, Rita K. (World Bank, Washington, DC, 2018)
Skills and Jobs in Brazil: An Agenda for Youth is a new report focusing on the challenge of economic engagement among the Brazilian youth. In the context of a fast aging population, Brazil’s greatest economic opportunity is to increase its labor productivity, especially that of youth. This report documents important new facts about the extent of the youth economic disengagement, while at school and at work. Today, close to half of the Brazilian youth aged 15-29 years old is not fully economically engaged, because they are neither working nor studying, are studying in schools of poor quality, or are working in informal and precarious jobs. The report shows how the youth prospects in the labor market are dimmed by policies favoring existing workers over new entrants; in addition, it shows how youth are often ill equipped to meet an increasingly challenging labor market. The report suggests new education, skills, and jobs policy changes that Brazil could prioritize moving forward, so that it can take advantage of the last wave of its demographic transition. The report discusses in particular depth policies aiming to increase learning and reduce school dropouts in upper secondary education, and labor market policies that aim to support more effective and faster youth transitions from school to work.